2014
DOI: 10.1002/cmdc.201402050
|View full text |Cite
|
Sign up to set email alerts
|

6‐Hydroxybenzothiophene Ketones: Potent Inhibitors of 17β‐Hydroxysteroid Dehydrogenase Type 1 (17β‐HSD1) Owing to Favorable Molecule Geometry and Conformational Preorganization

Abstract: The inhibition of 17β-hydroxysteroid dehydrogenase type 1 (17β-HSD1), which catalyzes the conversion of estrone into the potent estrogen receptor agonist estradiol (E2), is discussed as a novel therapeutic approach for the treatment of estrogen-dependent diseases. Because the reduction of E2 would be basically limited to the target tissues, this approach is expected to cause fewer side effects than the currently employed antihormonal therapies. Recently, we reported on 6-hydroxybenzothiazole ketones as a new c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Several authors have proposed the use of HSD17B1 inhibitors for breast cancer, either as a single treatment, conceivably once resistance to aromatase inhibitors has arisen, or in combination with other treatments [46, 71, 72]. The primary result of such inhibition would be the reduction of E2 levels and increased DHT levels in the tissues that express HSD17B1 [39, 44–46], and as such, side effects should be more limited than current anti-hormonal treatments due to the limited tissue expression of HSD17B1 in placenta, ovary [6] and breast epithelium [35, 36].…”
Section: Inhibitors Of Hsd17b1 and Hsd17b2mentioning
confidence: 99%
“…Several authors have proposed the use of HSD17B1 inhibitors for breast cancer, either as a single treatment, conceivably once resistance to aromatase inhibitors has arisen, or in combination with other treatments [46, 71, 72]. The primary result of such inhibition would be the reduction of E2 levels and increased DHT levels in the tissues that express HSD17B1 [39, 44–46], and as such, side effects should be more limited than current anti-hormonal treatments due to the limited tissue expression of HSD17B1 in placenta, ovary [6] and breast epithelium [35, 36].…”
Section: Inhibitors Of Hsd17b1 and Hsd17b2mentioning
confidence: 99%
“…A systemic bioisosteric replacement of benzothiazole by other heterocycles resulted in the identification of potent and selective 17β-HSD1 inhibitors bearing a benzothiophene moiety. Compound 44 (figure 9) is more active towards the target enzyme and displayed better selectivity over 17β-HSD2 than its benzothiazole analog 42(Miralinaghi et al 2014).Thiophenepyrimidinones. Messinger et al identified 17β-HSD1 inhibitors by computer aided drug design starting from a unique nonsteroidal pyrimidinone core (structure 45, figure 10) by optimizing R1 and R2.…”
mentioning
confidence: 99%
“…Starting point for the design was the class of bicyclic substituted hydroxyphenylmethanones (BSHs). [27][28][29] In contrast to most other classes of 17β-HSD1 inhibitors described by us [30][31][32][33][34][35][36][37][38], it contains members which not only are strong inhibitors of the human enzyme but also show inhibition of the murine ortholog (previously unpublished results, fig.2). Examples are compounds D and E ( fig.…”
Section: Figurementioning
confidence: 95%